Longitudinal changes in lung function and respiratory symptoms in progressive systemic sclerosis. Prospective study - Greenwald, G I; Tashkin, D P; Gong, H; Simmons, M; Duann, S; Furst, D E; Clements, P (The American journal of medicine, 1987)
Most patients with progressive systemic sclerosis (PSS) exhibit lung involvement. However, the natural history of lung disease in PSS remains poorly defined. To evaluate lung function over time in PSS, a battery of lung function tests were prospectively performed serially between 1973 and 1982 in 61 patients with PSS. Functional indexes of restriction (vital capacity and total lung capacity) and diffusion impairment (diffusing capacity) showed greater-than-expected annual rates of change. Male subjects showed a trend toward faster declines in forced vital capacity, forced expired volume in one second, total lung capacity, and functional residual capacity and a more rapid increase in static recoil pressure at 90 percent of total lung capacity than did female subjects. Nonsmokers had greater rates of decline in total lung capacity and static lung compliance (but not in forced vital capacity or diffusing capacity) and a greater rate of increase in static recoil pressure than did current and former smokers. Level of lung function at initial study visit, age, race, and chlorambucil therapy had no significant effect on the annual rates of change in lung function, whereas longer duration of disease prior to study entry was associated with a slower annual decrease in lung volumes. Between the first and last visits (mean interval 3.1 years, maximum nine years), the frequency of abnormality in pulmonary function test results showed significant change only in the diffusing capacity (60 percent increasing to 82 percent) and static lung compliance (40 percent increasing to 54 percent), whereas the frequency of respiratory symptoms showed little change. These findings indicate an overall indolent progression of PSS-related lung disease, with substantial individual variability.